TASK-BASED TEACHING OF THE ENGLISH LANGUAGE - N.I.Turayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Task-based teaching (TBT) is a communicative approach to language instruction that prioritizes meaningful tasks as a medium for learning. Instead of focusing on grammar rules and rote memorization, TBT engages learners in real-life tasks, such as solving problems, planning activities, or participating in role-plays, to develop fluency and accuracy. Rooted in the theories of communicative language teaching (CLT), this methodology emphasizes learner interaction, collaboration, and the integration of language skills in authentic contexts. Key proponents like Ellis (2003) and Nunan (2004) argue that TBT mirrors real-world communication, thereby preparing learners for practical language use. It incorporates a structured framework comprising pre-task, task, and post-task phases, each focusing on different aspects of language acquisition. The approach has been shown to boost learner motivation, foster teamwork, and enhance communicative competence.